Pendekatan Kolaboratif Dalam Pembelajaran Suatu Strategi Meningkatkan Interaksi Dan Hasil Belajar Peserta Didik - Lismayana Sahabuddin; Syamsul, Herawati; Nur Oktaviani (Journal of Society and Scientific Studies, 2026)
Meaningful learning processes not only focus on the transfer of knowledge from teacher to students, but also on the development of social skills, critical thinking abilities, and cooperation. In this context, collaborative approaches in learning become increasingly relevant and necessary strategies, especially in facing the challenges of 21st-century learning, which emphasize competencies in communication, collaboration, critical thinking, and creativity. Learning to build that meaning is carried out through direct experiences, communication, interaction, and reflection so that students can produce ideas that are meaningful. Therefore, learning is about producing ideas, not consuming ideas. The purpose of this study is to analyze the role of a collaborative approach in enhancing social interaction and learning outcomes of students in a formal educational environment. The type of research used is library research through literature review by combining a qualitative descriptive approach to empirical findings, namely a research process conducted naturally and genuinely according to objective conditions in the field without any manipulation of collected data, with an approach applied in the learning process to develop students' understanding in receiving the material being taught. The results of this study indicate that the collaborative approach has been proven to enhance social interaction and students' learning outcomes. Through models such as Jigsaw, Student Teams Achievement Divisions (STAD), Team-Based Learning (TBL), and Problem-Based Learning (PBL), students develop communication skills, teamwork, and conceptual understanding. The implementation of these strategies requires active teacher involvement, proper activity design, and continuous monitoring.